CHAP. 15] BOOLEAN ALGEBRA 391
Also, using the absorption law in the last step,
a+R=a+(a∗(b∗c))=(a+a)∗(a+(b∗c))=a∗(a+(b∗c))=a
Thusa+L=a+R. Next we show that a′+L=a′+R. We have,
a′+L=a′+((a∗b)∗c)=(a′+(a∗b))∗(a′+c)
=((a′+a)∗(a′+b))∗(a′+c)=( 1 ∗(a′+b))∗(a′+c)
=(a′+b)∗(a′+c)=a′+(b∗c)
Also,
a′+R=a′+(a∗(b∗c))=(a′+a)∗(a′+(b∗c))
= 1 ∗(a′+(b∗c))=a′+(b∗c)
Thusa′+L=a′+R. Consequently,
L= 0 +L=(a∗a′)+L=(a+L)∗(a′+L)=(a+R)∗(a′+R)
=(a∗a′)+R= 0 +R=R
( 8 a)Follows from( 8 b)and duality.
15.6. Prove Theorem 15.3: Letabe any element of a Boolean algebraB.
(i) (Uniqueness of Complement) Ifa+x=1 anda∗x=0, thenx=a′.
(ii) (Involution Law)(a′)′=a
(iii) ( 9 a) 0 ′=1;( 9 b) 1 ′=0.
(i) We have:
a′=a′+ 0 =a′+(a∗x)=(a′+a)∗(a′+x)= 1 ∗(a′+x)=a′+x
Also,
x=x+ 0 =x+(a∗a′)=(x+a)∗(x+a′)= 1 ∗(x+a′)=x+a′
Hencex=x+a′=a′+x=a′.
(ii) By definition of complement,a+a′=1 anda∗a′=0. By commutativity,a′+a=1 anda′∗a=0.
By uniqueness of complement,ais the complement ofa′, that is,a=(a′)′.
(iii) By boundedness law( 6 a),0+ 1 =1, and by identity axiom( 3 b),0∗ 1 =0. By uniqueness of complement,
1 is the complement of 0, that is, 1= 0 ′. By duality, 0= 1 ′.
15.7. Prove Theorem 15.4: (DeMorgan’s laws):( 10 a) (a+b)′=a′∗b′.( 10 b) (a∗b)′=a′+b′.
( 10 a)We need to show that(a+b)+(a′∗b′)=1 and(a+b)∗(a′∗b′)=0; then by uniqueness of complement,
a′∗b′=(a+b′). We have:
(a+b)+(a′∗b′)=b+a+(a′∗b′)=b+(a+a′)∗(a+b′)
=b+ 1 ∗(a+b′)=b+a+b′=b+b′+a= 1 +a= 1
Also,
(a+b)∗(a′∗b′)=((a+b)∗a′)∗b′
=((a∗a′)+(b∗a′))∗b′=( 0 +(b∗a′))∗b′
=(b∗a′)∗b′=(b∗b′)∗a′= 0 ∗a′= 0
Thusa′∗b′=(a+b)′.
( 10 b) Principle of duality (Theorem 15.1).